The Experience of Final Graduation Projects in the Basic Education Division of the Education Research and Teaching Center of the Universidad Nacional - Rodríguez Araya, María Roxana (2014)
This paper studies the process experienced by graduate students and the academic staff in the Licentiate level [university degree between the Bachelor’s and the Master’s] during the execution of their final graduation projects in the Basic Education Division.  The need to evaluate the process results from a continuing reflection by the Division’s Administration.  In order to understand the information obtained from the database, data was grouped by academic programs with the purpose of analyzing their individual processes.  Using the Pearson´s chi-square test, results show that there are significant differences (p≤ 0.05) between final graduation projects for the different programs.  Due to these results, it is necessary to identify the factors that differentiate the programs and that promote the successful conclusion of the final graduation project.